2005
DOI: 10.1191/0960327105ht563oa
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute cadmium toxicity by Picroliv

Abstract: The potential of Picroliv, a herbal extract against acute cadmium (Cd) intoxication, was evaluated in male rats. Biochemical and histopathological profile in rats pretreated with Picroliv (12 mg/kg, oral) followed by a single dose of Cd as cadmium chloride (CdCl2) (3 mg/kg, ip) revealed marked suppression of oxidative stress in liver and testes. The Cd-induced enhanced levels of lipid peroxidation, membrane fluidity and reduced levels of nonprotein sulphydryls and Na+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Protection against acute and chronic Cd toxicity by reducing oxidative stress has been reported by many groups (Sunitha et al 2001;Khandelwal et al 2002;Shaikh and Tang 2002;Ray et al 2002;Yadav et al 2005). Similarly in our studies, antioxidant property could be one of the main triggering factors, responsible for mitigation of all downstream events initiating with ROS and GSH preceding mitochondrial membrane potential, caspase-3 activation followed by DNA damage and phenotypic alterations at 18 h and blastogenesis and cytokine release at a much later stage.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Protection against acute and chronic Cd toxicity by reducing oxidative stress has been reported by many groups (Sunitha et al 2001;Khandelwal et al 2002;Shaikh and Tang 2002;Ray et al 2002;Yadav et al 2005). Similarly in our studies, antioxidant property could be one of the main triggering factors, responsible for mitigation of all downstream events initiating with ROS and GSH preceding mitochondrial membrane potential, caspase-3 activation followed by DNA damage and phenotypic alterations at 18 h and blastogenesis and cytokine release at a much later stage.…”
Section: Discussionsupporting
confidence: 70%
“…Curcumin treatment also prevented the GSH oxidation and maintained GSH/GSSH ratio in rats after oral administration of CCl 4 (Reyes- Gordillo et al 2007). Yadav et al (2005) and Yadav and Khandelwal (2008) have reported the antioxidative potential of picroliv in liver and testis of rats against cadmium. Cadmium induced enhanced lipid peroxidation, membrane fluidity and reduced levels of nonprotein sulphydryls and Na + K + ATPase were significantly restored by picroliv.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, some phytochemicals and plant extracts with antioxidative properties have been found to have the capacity to decrease tissue cadmium levels and cadmium-induced oxidative stress (15)(16)(17)(18). Such natural compounds have few side effects, and some of them can be served as dietary nutritional ingredients.…”
mentioning
confidence: 99%
“…The supplementation of vanaspati with ferrous sulfate resulted in an elevated activity of ALP. The results are in accordance with those of Demerdesh et al .,[ 11 ] Kara et al ,[ 12 ] and Yadav et al .,[ 13 ] who reported an increase in the activities of ALT and ALP in plasma following cadmium toxicity.…”
Section: Resultsmentioning
confidence: 99%